CEO Emotional Intelligence and Firms' Financial Policies. Bayesian Network Method - Mohamed Ali Azouzi; Anis Jarboui (Contemporary Economics, 2014)
The aim of this paper is to explore the determinants of firms' financial policies according to the manager's psychological characteristics. More specifically, it examines the links between emotional intelligence, decision biases and the effectiveness of firms' financial policies. The article finds that the main cause of an organization's problems is the CEO's emotional intelligence level. We introduce an approach based on Bayesian network techniques with a series of semi-directive interviews. The research paper represents an original approach because it characterizes behavioral corporate policy choices in emerging markets. To the best of our knowledge, this is the first study in the Tunisian context to explore this area of research. Our results show that Tunisian leaders adjust their decisions (on investments and distributions) to minimize the risk of loss of compensation or reputation. They opt for decisions that minimize agency costs, transaction costs, and cognitive costs.
Keywords: G14; G31; G32; D80; 330; emotional intelligence; corporate finance; optimism; overconfidence; loss aversion; financial policy; Bayesian network